2018
DOI: 10.1155/2018/3951540
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Duckweed (Lemna minor) for the Phytoremediation of Landfill Leachate

Abstract: Phytoextraction of zinc, copper, lead, iron, and nickel from landfill leachate by duckweed (L. minor) was investigated every 3 days over a period of 2 weeks. Bioconcentration factor and removal efficiency were also calculated. Results of this study proved that L. minor significantly reduced the concentration of heavy metals in landfill leachate. Removal efficiency of L. minor, for all the metals, from landfill leachate was more than 70% with the maximum value for copper (91%). Reduction in chemical oxygen dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 58 publications
1
33
0
7
Order By: Relevance
“…These are the plants with floating leaves and submerged roots. Some of the free-floating aquatic plants are well recognized for their capability to eliminate the metals from the contaminated environment: water hyacinth (Eichhornia crassipes) [128], water ferns (Salvinia minima) [129], duckweeds (Lemna minor, Spirodelaintermedia), [130,131], water lettuce (Pistiastratoites), [132], water cress (Nasturtium officinale) [133]. The potential of these free floating aquatic plant for the elimination of heavy metals is comprehensively studied in different studies [99,134,135].…”
Section: Free-floating Aquatic Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the plants with floating leaves and submerged roots. Some of the free-floating aquatic plants are well recognized for their capability to eliminate the metals from the contaminated environment: water hyacinth (Eichhornia crassipes) [128], water ferns (Salvinia minima) [129], duckweeds (Lemna minor, Spirodelaintermedia), [130,131], water lettuce (Pistiastratoites), [132], water cress (Nasturtium officinale) [133]. The potential of these free floating aquatic plant for the elimination of heavy metals is comprehensively studied in different studies [99,134,135].…”
Section: Free-floating Aquatic Plantsmentioning
confidence: 99%
“…The capability of duckweed plant to develop in polluted site with tremendous variation in pH, temperature, nutrient level makes them effective for use in phytoremediation [207]. Duckweed can eliminate a vast variety of different heavy metals, inorganic and organic contaminants, pesticides, nutrients arise from agricultural runoff, sewage, industrial and domestic wastewater [131,138,208]. Duckweed can easily inhibit the growth of algae and fungi in different ponds because it has the ability to cover the ponds due to its widespread high growth rate.…”
Section: Duck Weedmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, further purification was assured by the assimilation of duckweed. Mackenzie et al, 2003;Daud et al, 2018 have researched and reported the potential of the aforementioned species individually can reduce the total metal concentration levels up to 70% associated with a BOD, COD, pH, TSS, and TDS removal of around 45%, 40%, 15%, 35%, and 40% respectively through the phytoremediation mechanism, which is good enough to stand alone. Despite, the present research work has recorded a significantly lower level of efficacy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The same mechanism is replicated by the duckweed as well. The harvesting technique is also quite simple and inexpensive in the case of smaller constructed wetland system (Mackenzie et al, 2003;Daud et al, 2018). Approximately 70% of the atmospheric oxygen gets generated due to the autotrophic activity of the microalgae.…”
Section: Introductionmentioning
confidence: 99%